Hydrothermal Synthesis and Crystal Structure of Binuclear Complex [Cd(5-ClHsal)2(2,2'-bipy)]2 - Jiang, Xiu-Rong; Dong, Yan; Chen, Wu-Hua; Wen, De-Cai (Asian Journal of Chemistry, 2012)
A novel cadmium complex [Cd(5-ClHsal)2(2,2'-bipy)(H2O)]2 (5-ClHsal = 5-chlorosalicylate anion, 2,2'-bipy = 2,2'-bipyridine) was synthesized by hydrothermal reaction and characterized by elemental analysis and X-ray single crystal diffraction. The crystal is monoclinic, space group P21/c with a = 9.138(3) Å, b = 17.174(6) Å, c = 16.174(5) Å, a = 90º, b = 106.06(1)º, g = 90°, Mr = 1259.41, V = 2439(1)Å3, Dc = 1.715 g/cm3, F(000) = 1256 and Z = 2. The structure analysis shows that the complex exhibits a binuclear structure. The adjacent binuclear molecules are connected together by the hydrogen bonds to 1D supramolecular chain structure. The crystal structure is stabilized by hydrogen bonds and p-p stacking interactions.